Conservation of quantity and quality of petroleum products in storage - Бойченко, C. B.; Бойченко, О. В.; Литвинов, A. A.; Еременко, С. М. (Proceedings of National Aviation University (archive), 2000)
Considered, analysed and systematized are the data concerning technical means of protection of petroleum products losses by evaporation. Presented is analysis of physical, chemical and organizational measures aimed at solution of problems of irrevocable losses of oil and petroleum products caused by evaporation. In order to prevent natural losses of oil and petroleum products in tank great attention is to be paid to perfection of breathing and safety devices of the tanks. The most interesting among the developed ones is thermoelectric cooler condenser working principle of which consists in Peltier effect discovered in 1834